Stress Management on Senior High School Students in Semarang - Dwi Heppy Rochmawati; Wigyo Susanto; Hetty Catur Ellyawati (Indonesian Journal of Global Health Research, 2021)
Stress is a mental emotional disorder faced by a person due to pressure. Such pressure arises from the failure of individuals to fulfill their needs or wants. The pressure felt by someone can come from within or from outside of themselves. Individuals who experience stress need proper management, so as not to cause further harmful effects. One of the stress management method is by providing 5-finger technique therapy. The purpose of this study was to determine the effect of the 5-finger technique on the high school students’ stress level in Semarang. This study used a Quasi-Experiment Pretest-Posttest design without a control group. The instrument used was a 5-finger technique therapy worksheet, while the stress level was measured using the DASS-42 (Depression Anxiety Stress Scale). Approximately 90 respondents were chosen through simple random sampling and met the including criteria. The data analysis was conducted by using Mann Whitney statistical test, obtaining p-value <0.05 (0.00) was obtained with a decrease in the respondents’ stress level. The results showed that the 5-finger technique reduced the respondents’ stress level.